Nutritional and amino acid composition of red tilapia fish (Oreochromis niloticus) - Roslan, Jumardi; Mustapa Kamal, Siti Mazlina; Md. Yunos, Khairul Faezah; Abdullah, Norhafizah (Faculty of Engineering, Universiti Putra Malaysia, 2012)
Tilapia has received much attention to be used as a source of food protein. In making tilapia fish as a source of food protein, there are many by-products (head, frame, and tail) produced during the processing of fish which are usually discarded. The nutritional properties of tilapia muscle and by products were quantitatively determined. It was found that the proximate compositions of tilapia muscle were 18.59 ± 0.35% of crude protein content, 80.66 ± 0.48% of dry matter content, 1.15 ± 0.07% of ash, 0.38 ± 0.06% of oil content and 27.02±0.30 mg/g of soluble protein content. While for tilapia by-product were 14.60 ± 0.30% of crude protein content, 66.57 ± 0.39% of dry matter content, 8.93 ± 0.46% of ash, 5.50 ± 0.30% of oil content and 25.83 ± 0.45 mg/g of soluble protein content. Identification of amino acids composition on tilapia muscle and by product have found that the total amino acid content were 93.08 ± 1.08 g/kg and 92.80 ± 1.48 g/kg respectively while the essential amino acid were 36.57 ± 0.51 g/kg and 31.38 ± 0.51 g/kg respectively. The most abundant amino acid in tilapia muscle was glutamic acid (15.94 ± 0.22 g/kg), while for tilapia by product was glycine (14.35 ± 0.22). Lysine was the most abundant essential amino acid in tilapia muscle and by product (7.03 g/kg and 5.55 g/kg respectively). These results indicate that tilapia fish has excellent source of protein, particularly an essential amino acids such as lysine. Along with a growing interest in food protein to be used as food ingredient, it appears tilapia fish has very good potential to serve as source of protein.